2019
DOI: 10.1080/17583004.2018.1544830
|View full text |Cite
|
Sign up to set email alerts
|

Carbon mineralization in soil as influenced by crop residue type and placement in an Alfisols of Northwest India

Abstract: Carbon (C) mineralization of crop residues is an important process occurring in soil which is helpful in predicting CO 2 emission to the atmosphere and nutrient availability to plants. A laboratory experiment was conducted in which C mineralization of residues of rice (Oryza sativa), wheat (Triticum aestivum), maize (Zea mays), mungbean (Vigna radiata) and their mixtures was applied to the soil surface or incorporated into an Alfisols from Northwest India. C mineralization was significantly affected by residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 33 publications
4
21
0
1
Order By: Relevance
“…And indeed, higher DOC was associated with higher respiration in the sandy Cambisol compared to the clay Vertisol. According to this interpretation, Li et al (2013) and Datta et al (2019) found higher emissions for residues placed on the soil surface than for incorporated residues as was the case in our experiment with the Vertisol. This indicates that the incorporation of residues into the soils in our study inhibited CO 2 release, by modifying the availability of resources and oxygen to decomposers and gaseous diffusion from soil pores to the atmosphere.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…And indeed, higher DOC was associated with higher respiration in the sandy Cambisol compared to the clay Vertisol. According to this interpretation, Li et al (2013) and Datta et al (2019) found higher emissions for residues placed on the soil surface than for incorporated residues as was the case in our experiment with the Vertisol. This indicates that the incorporation of residues into the soils in our study inhibited CO 2 release, by modifying the availability of resources and oxygen to decomposers and gaseous diffusion from soil pores to the atmosphere.…”
Section: Resultssupporting
confidence: 71%
“…However, we found that the absolute difference in the soil respiration of the Vertisol was lower when residues were incorporated than when left on the surface if compared to control. Such a discrepancy may have arisen from the ability of clay to slow down the organic matter decomposition by absorption, interacting with soil microbes and their external enzyme activity or by limiting oxygen diffusion and CO 2 release (Vogel et al 2015, Datta et al 2019. And indeed, higher DOC was associated with higher respiration in the sandy Cambisol compared to the clay Vertisol.…”
Section: Resultsmentioning
confidence: 99%
“…Conservation tillage had significantly higher concentrations of P and K in soil compared to conventional tillage (Table 4) and was associated with residue incorporation and their decomposition, which causes recycling of nutrients present in the residues [64,65] and improves nutrient status of N, P, and K in the soil [66,67]. The results of available P (Table 4) showed the higher concentration of nutrients on the surface which agrees with the study of Jat et al [47] who reported that Olsen P concentration was 38% and 25% higher under straw management practices and conservation tillage compared to conventional farmer's practices at top soil surface [47].…”
Section: Soil Physio-chemical Properties Under Tillage-residue Management Practicesmentioning
confidence: 99%
“…There are a wide range of management practices having the potential to increase resource use efficiency, improve adaptive capacity while reducing the environmental footprint from the production system, and are defined as climate-smart agriculture (CSA) practices ( FAO, 2010 ; Jat et al, 2016 ). Among different CSA practices; zero-till direct drilling, crop residue retention, crop diversification, and precision nutrient and water management are considered key to positively influence crop productivity and soil health ( Ghimire et al, 2017 ; Jat et al, 2018 , 2019a , b ; Datta et al, 2019 ) while adapting to climatic risks and reducing green house gas (GHG) emissions ( Sapkota et al, 2015 ; Jat et al, 2016 ). However, the application of CSA practices in isolation may or may not play its potential role in adapting to climate risks in the intensive agri-food systems of the IGP.…”
Section: Introductionmentioning
confidence: 99%